Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.actbio.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Semi-degradable poly(β-amino ester) networks with temporally controlled enhancement of mechanical properties

Abstract: Biodegradable polymers are clinically used in numerous biomedical applications, and classically show a loss in mechanical properties within weeks of implantation. This work demonstrates a new class of semi-degradable polymers that show an increase in mechanical properties through degradation via a controlled shift in a thermal transition. Semi-degradable polymer networks, poly(β-amino ester)-co-methyl methacrylate, were formed from a low glass transition temperature crosslinker, poly(β-amino ester), and high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As it becomes eminently important to engineer materials with specific lifetimes for drug release, for patterning of porous materials, and to avoid plastic persistence in landfills, PBAEs with lifetimes that range from hours to months are increasingly attractive components of advanced materials 7,13 . To expand the usefulness and scope of PBAEs, including for use as shape‐memory thermosets, 14–16 elastomers, 7,13,17,18 controlled release drug delivery vehicles, 19‐23 and degradable hydrogel cross‐linkers, 24–27 a thorough understanding of their degradation and solution behavior is needed.…”
Section: Introductionmentioning
confidence: 99%
“…As it becomes eminently important to engineer materials with specific lifetimes for drug release, for patterning of porous materials, and to avoid plastic persistence in landfills, PBAEs with lifetimes that range from hours to months are increasingly attractive components of advanced materials 7,13 . To expand the usefulness and scope of PBAEs, including for use as shape‐memory thermosets, 14–16 elastomers, 7,13,17,18 controlled release drug delivery vehicles, 19‐23 and degradable hydrogel cross‐linkers, 24–27 a thorough understanding of their degradation and solution behavior is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed in the DMA T g data (Figure D). Transition according to the DSC data is occurring at lower temperatures than according to DMA, which is explained by the differences in how T g is defined for both methods . The upward shift in T g after longer drying periods indicates a plasticizing effect of the solvent (ethyl acetate) and the additional cross-linking that is occurring to some extent after printing during the drying process.…”
Section: Resultsmentioning
confidence: 95%
“…All the curves show the expected glassy region followed by a transition region leading to the rubbery plateau of the cross-linked network. 59,60 Modulus values of the rubbery plateau increase with increasing thiol amounts and thus increasing cross-link density of the material, where the 5:1 alkene:thiol samples show the highest modulus values at the rubbery plateau for all three different drying times (2, 4, and 8 days, Figure 2A−C) and 30:1 samples show the lowest modulus values at the rubbery plateau. The moduli values in the glassy region are similar for different alkene:thiol ratios; thus, the range of the transition region decreases with increasing cross-link density, as expected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Poly(-amino ester)s (PBAEs) are an important class of biodegradable synthetic polymers which are being investigated as gene [8][9][10][11][12][13][14][15] and drug [16][17][18][19][20][21] delivery vehicles and tissue engineering scaffolds [22][23][24][25][26][27][28][29][30][31][32][33][34] due to their pH sensitivities, biodegradabilities and high biocompatibilities. They are easily prepared by Michael addition of difunctional amines to commercial diacrylates under mild conditions and are degradable to diols, bis(-aminoacids), and poly(acrylic acid) chains under physiological conditions by cleavage of ester linkages due to hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PBAE macromers were used as crosslinkers for the synthesis of 2-hydroxyethyl methacrylate (HEMA) and N-vinylpyrrolidone (NVP) hydrogels to enhance the hydrogels' swelling and degradation properties [31]. Semi-degradable polymer networks, copolymers of PBAE macromers and methyl methacrylate, were prepared to control and enhance mechanical properties during degradation [32,33]. It was shown that as the low T g component degrades, the T g of the network and hence its modulus increases to give materials with tailorable toughness.…”
Section: Introductionmentioning
confidence: 99%